Electronic games through digital technology and its impact on the personality and culture of the child (Psychoanalytic reading) (Journal of Human Sciences, 2022)
The current study aimed to review the most important future challenges faced by digital literature and digital culture for Arab children, through a statement of the results of previous studies that discussed the widespread spread of electronic games through digital technology means as an important part of electronic culture and its effects on children’s literature and culture, as well as In terms of discussing the impact of the psychological, social, and ethical aspect of digital culture, and the issues, elements and psychological conditions related to it. The culture of the Arab child includes the entire process of socialization based on the formation of the child’s Arab personality and belonging to his national culture and laying the foundations of his Arab and Islamic identity. The researcher relied on the descriptive approach to reach the results of the study, the most important of which are: that there is an underlying danger behind games, which is electronic addiction. Philosophical, scientific and educational, and communicating with them to come up with various studies on children’s culture and literature in form and content, with the aim of raising the psychological, social, moral, intellectual and scientific level of children through literature and culture in general and digital in particular.